Behavior of thin reinforced concrete slabs and effect of reinforcement bars subjected low-velocity impact. (April 2022) - Mizushima, Yasunori; Iino, Natsuki
Abstract: Low-velocity impacts of thin reinforced concrete (RC) slabs are considered in accidental falling objects during building constructions. In such scenario, reinforcement bars may show resistance against perforation. If the effect of reinforcement bars against perforation behavior of RC slabs can be evaluated, it allows more rational protection and construction planning. In this study, an experimental and numerical investigation has been presented to evaluate the effect of reinforcement bars on perforation behaviors of thin RC slabs subjected to low-velocity impacts assuming accidental falling objects onto underlying slabs during building construction. Two impact tests were performed with impact energy and reinforcement amount as parameters. The experimental results show that increasing the amount of reinforcement leads to increased perforation resistance. To evaluate the effect in greater depth, a numerical analysis was performed with varying reinforcement arrangements and impact energy. The analytical result reproduced the behavior of the RC slabs observed in the experiment including perfect perforation. The numerical results have shown that the perforation resistance of the slabs improved with the increasing amount of reinforcement, even under conditions other than those in the experiment. Furthermore, based on the experiment and analysis, a perforation resistance mechanism has been proposed for reinforcement bars in a range beyond the perforation limit calculated by the empirical formula, and the calculated results based on this mechanism have corresponded to the perforation behavior of thin RC slabs obtained from the experiment and analysis.